Integrating Prophetic Leadership into Modern Strategic Agility: A Literature Synthesis for Sharia-Based Organizations in the Digital Era - Aisyah Sukata (CV. ALIM'SPUBLISHING, 2026)
This study presents a comprehensive synthesis regarding the integration of prophetic leadership models into modern strategic agility frameworks for sharia-based organizations navigating the digital era. The introduction emphasizes the urgency of the research, driven by massive digital disruption that demands organizations to respond to market dynamics swiftly without compromising ethical principles and sharia compliance. The method explains the systematic literature review approach applied to select, review, and extract data from high-reputability literature indexed in Scopus, Web of Science, and Sinta databases. The theoretical framework analyzes contemporary strategic agility concepts alongside Islamic epistemology. The results describe that the integration of prophetic values functions as a crucial catalyst in managing digital transformation holistically and avoiding technocentric biases. The analysis and discussion examines these findings against contemporary meta-capability theories, revealing that integrating Siddiq and Amanah values significantly strengthens leadership unity and builds virtual integrity. Furthermore, the Fathanah value is identified as an essential driver for strategic sensitivity that generates pedagogical and operational discretion, while the Tabligh value facilitates effective omnichannel advocacy. This synthesis produces a hybrid governance design and a highly resilient Digital Prophetic Leadership framework. The conclusion contains the formulation that the application of prophetic leadership on digital platforms successfully balances technological innovation with theological mandates, ultimately producing entities that are agile, resilient, and comprehensively ethical.